Technological, Sensorial and Nutritional Meat Quality Traits from Pig Fed with Conventional and Unconventional Diets - Hedji, C. Carine; HOUNDONOUGBO, M. FRÉDÉRIC; TOUGAN, P. ULBAD; HOUINATO, MARCEL ROMUALD BENJAMIN; FIOGBE, EMILE DIDIER (My University, 2015)
The aim of the study was to evaluate the impact of unconventional food resources on the quality of pig meat. 90 pigs of which 20 were slaughtered at 180 days old for meat quality evaluation. It came out from the study that the highest L* and b* were obtained in A0 commercial feed, while the highest a* was recorded in A3 (P < 0.05). From 45 minutes to 24 h post-mortem, the highest pork hue value was recorded in A2, whereas the highest chromaticity was found in A0. The pH 45 and pH 24 of Mld (Muscle Longissimus dorsi) were lower in control group than in experimental groups. The cooking loss and water-holding capacity of the meat from A4 were higher than those of other treatments. Luminance, redness, yellowness, chroma values and pH of the pork had increased during the post-mortem aging time for the both diet treatments while the hue value decreased (P < 0.05). Nutritionally, the protein content, the fat content, the dry matter content and the ash content varied respectively from 24.45% to 26.87%, 0.52% to 1.6%, 26% to 27.5% and 1.1% to 1.79% with the highest protein contents found in meat from unconventional feed A4 (P < 0.01) while the highest fat content (1.6%) was obtained from meat of the control group A0 (P < 0.001). The texture of the meat from the control group was better than those of experimental groups (P < 0.01). Overall, unconventional diet based on Azolla and Moringa improves technological and nutritional pork quality.
Keywords: Pig; Meat Quality; Unconventional Diet; Benin